Global burden of soil-transmitted helminth infections, 1990–2021 - Chen, Jin; Gong, Yanfeng; Chen, Qin; Li, Shizhu; Zhou, Yibiao (Infectious diseases of poverty, 2024)
Soil-transmitted helminth (STH) infections can cause a significant disease burden. It is estimated that 1.5 billion people worldwide are infected with STHs, primarily in tropical and subtropical regions. This study aimed to assess the distribution of the global burden and trend of STH infections from 1990 to 2021. We retrieved data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021 on the age-standardized rates (ASRs) of prevalence and disability-adjusted life-years (DALYs) of STH infections for all age groups in 204 countries and territories from 1990 to 2021. The ASRs of prevalence and DALYs by age, gender, and socio-demographic index (SDI) were calculated to quantify the spatial distribution and temporal trend. Spearman correlation analysis was used to examine the relationship between ASR and SDI. In 2021, there were an estimated 642.72 million cases and 1.38 million DALYs caused by STH infections worldwide. The age-standardized prevalence rate (ASPR) of STH infections was 8429.89 [95% uncertainty interval (UI): 7697.23, 9362.18 ] per 100,000 population globally. The ASPR of STH infections varied across 21 geographic regions in 2021, being mainly prevalent in most African and Latin American locations. The prevalence was higher in the groups of 5-19 years, especially the group of 5-9 years with the ASPR of 16,263 (95% UI: 14,877.06, 18,003.49) and ASR of DALYs of 40.69 (95% UI: 25.98, 60.91) per 100,000. The ASPR of STH infections showed an obvious decreasing trend worldwide (estimated annual percent change = - 4.03, 95% confidence interval: - 4.13, - 3.93) with variations in different species infections during the study years. At the regional level, the ASR of STH infections prevalence (r = - 0.8807, P < 0.0001) and DALYs (r = - 0.9069, P < 0.0001) were negatively correlated with SDI . STH infections remain a public health problem in 2021, particularly in regions such as the middle parts of Africa and Americas, and in the 5-19 age populations. The reduction in the rate of prevalence and the loss of DALYs are negatively correlated with the increase in SDI. Enhancing political commitment, providing accurate preventive chemotherapy, and advancing techniques for surveillance and mapping systems are essential to achieve the target of ending STH infections as a public health problem by 2030.